Senam Lansia Di Desa Padang Laru Kec. Panyabungan Timur Kab. Mandailing Natal - Nasution, Helmi Wardah; Desi , Ferika; Batubara , Khoirunnisaa; Tinendung , Dewi Sri Rahayu (Cattleya Darmaya Fortuna, 2024)
In Indonesia, the proportion of the elderly population continues to grow. Indonesia is among the top five countries with the highest number of elderly people in the world, reaching 18.1 million in 2010. The increasing of population and life expectancy of the elderly will cause various problems among other health problems, psychological and socio-economic. One of the problems in the elderly is a decrease in activity due to aging is characterized by a lack of motivation to follow gymnastics elderly. This is caused by a lack of knowledge about gymnastics elderly. The purpose of this study was to identify the description of the elderly knowledge about gymnastics. This research is using quantitative descriptive method, with sample data retrieval technique using total sampling. The number of respondents who took as many as 29 elderly people in social institutions Tresna Werdhana Budi Pertiwi. Instrument using questionnaires and data analysis techniques using frequency distribution. The results of the research showed that the frequency distribution of respondents by age 60-74 years (48.3%) or more of the mostly elderly knowledgeable both 14 elderly (48.3%), and the elderly who are knowledgeable enough 14 elderly (48.3%) and No less knowledgeable one elderly (3.4%). From these results it can be concluded that nearly half (48.3%) and fairly good knowledge. As for advice for health workers is holding counseling about gymnastics elderly. Keywords: Knowledge, Gymnastics Elderly, Elderly